2010
DOI: 10.2203/dose-response.09-015.mukherjee
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Dependency of Resveratrol in Providing Health Benefits

Abstract: ᮀ This review describes the dose-dependent health benefits of resveratrol, a polyphenolic antioxidant that is found in a variety of foods, especially grape skin and red wine. Resveratrol provides diverse health benefits including cardioprotection, inhibition of lowdensity lipoprotein, activation of nitric oxide (NO) production, hindering of platelet aggregation [32] A

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(181 citation statements)
references
References 116 publications
(169 reference statements)
4
173
0
4
Order By: Relevance
“…The crucial point in the effect of RES is the dose-dependency. RES has been reported as beneficial at lower dose wheras it has apoptotic actions at higher dose 37) . Therefore the dose-dependent response of cells against RES (0.25-100 µM) was investigated in the first phase of the study.…”
Section: Discussionmentioning
confidence: 99%
“…The crucial point in the effect of RES is the dose-dependency. RES has been reported as beneficial at lower dose wheras it has apoptotic actions at higher dose 37) . Therefore the dose-dependent response of cells against RES (0.25-100 µM) was investigated in the first phase of the study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review by Mukherjee et al (2010), showed a dose dependent effect of resveratrol: i.e. at lower doses it can be very useful in maintaining human health, while at higher doses, resveratrol has pro-apoptotic effects on healthy cells, but can also kill tumour cells.…”
Section: Resultsmentioning
confidence: 99%
“…Secara umun resveratrol memperlihatkan efek bifasik, dosis kecil memperlihatkan efek antioksidan, sedangkan dosis tinggi malah memperlihatkan efek pro-oksidan. 16 Bukti lain memperlihatkan bahwa efek antioksidan RSV bersifat dosedependent, semakin tinggi dosis RSV akan dapat memberikan efek antioksidan yang semakin besar. 17 Rentang dosis RSV untuk antioksidan yang telah diujikan sampai saat ini sangat lebar, pada uji preklinik berkisar 5-500 mg/kgBB/hari dan pada uji klinik 5-5.000 mg/hari.…”
Section: Gambar 3 Nukleoid Limfosit Hasil Pemeriksaan Comet Assay Heunclassified